Re: Ashley M. Hopkins, Ganessan Kichenadasse, Christos S. Karapetis, et al. Concomitant Proton Pump Inhibitor Use and Survival in Urothelial Carcinoma Treated with Atezolizumab. Clin Cancer Res. In press. https://doi.org/10.1158/1078-0432.CCR-20-1876 - Satoshi Funada; Takashi Yoshioka; Yan Luo (European Urology Oncology, 2020)
On May 15, 2025, the Food and Drug Administration approved retifanlimab in combination with carboplatin and paclitaxel for treating unresectable or metastatic squamous cell carcinoma of the anal canal (SCAC), and as a single agent for second-line SCAC treatment. These approvals were based on POD1UM-303 and POD1UM-202 trials. In POD1UM-303, 308 patients with no prior systemic treatment for advanced disease were randomized 1:1 to receive retifanlimab or placebo, both combined with carboplatin and paclitaxel. The primary efficacy outcome was progression-free survival (PFS) assessed by blinded independent central review, with overall survival (OS) as a key secondary endpoint. The trial demonstrated a statistically significant PFS improvement with a hazard ratio (HR) of 0.63 (95% CI: 0.47, 0.84, p-value 0.0006). Median PFS was 9.3 months (95% CI: 7.5, 11.3) and 7.4 months (95% CI: 7.1, 7.7) in the retifanlimab and placebo arms, respectively. Interim OS results were not statistically significant (HR 0.70 [95% CI: 0.49, 1.01]), although the point estimate for OS was 29.2 months (95% CI: 24.2, NE) in the retifanlimab arm and 23 months (95% CI: 15.1, 27.9) for placebo. Second-line approval was based on POD1UM-202, a single-arm trial of 94 patients receiving single-agent retifanlimab. The independent centrally assessed overall response rate was 14% (95% CI: 8, 23). No new adverse safety signals were identified. The approval of retifanlimab as a single agent or in combination with chemotherapy provides a new therapeutic option for patients with unresectable or metastatic SCAC.